Penggunaan Media Kubus Satuan dengan Model PBL untuk Meningkatkan Hasil Belajar Matematika Kelas V - Nurbaiti Rahmah; Sunarno Sunarno (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
The problem in this study is the low learning outcomes of fifth-grade students of SDN Kuin Utara 7 Banjarmasin on the volume of cuboids. This is caused by the lack of active student involvement in learning, minimal use of concrete media, and limited contextual practice questions. This study aims to analyze student activities and learning outcomes through the use of unit cube media with the Problem Based Learning (PBL) model. This study is a Classroom Action Research (CAR) carried out in two cycles. The subjects of the study were 25 fifth-grade students of the 2024/2025 academic year. Qualitative data were obtained from observations of student activities, while quantitative data were obtained through learning outcome tests. Data analysis was carried out using a percentage scale and classical learning completion indicators. The results showed that student activity increased from the category of "quite active" in cycle I to "very active" in cycle II. Student learning outcomes also increased, indicated by an increase in classical completion from cycle I to cycle II. It can be concluded that the use of unit cube media with the Problem Based Learning (PBL) model can improve student activity and learning outcomes on the volume of cuboids material in fifth-grade students.